Environment-friendly degradable food packaging bag and preparation method thereof
Patent Information
- Application Number
- CN202610789343.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-06-03
- Publication Date
- 2026-10-20
AI Technical Summary
目前市面上的可降解食品包装袋多采用PLA(聚乳酸)、PBAT(聚己二酸对苯二甲酸丁二酯)与淀粉简单共混的方式制备,虽能实现基本的降解功能,但存在诸多技术缺陷,无法满足食品包装的安全性、阻隔性、力学性能及多场景降解需求,具体如下:
1.结构独创,解决分层难题:采用三层梯度功能复合结构,外层侧重耐候印刷,中层侧重高阻隔增强,内层侧重抗菌疏水,三层组分梯度适配,通过分子链穿插+弱氢键自粘合实现无胶复合,彻底解决现有可降解包装袋层间结合力弱、易分层剥离的技术痛点,层间剥离强度≥1.7N/15mm。
Abstract
Description
Technical Field
[0001] This invention belongs to the field of food packaging materials technology, specifically relating to an environmentally friendly and biodegradable food packaging bag and its preparation method. Background Technology
[0002] With tightening environmental policies and increased consumer health awareness, biodegradable food packaging is gradually replacing traditional non-biodegradable plastic packaging, becoming the mainstream trend in the industry. Currently, most biodegradable food packaging bags on the market are prepared by simply blending PLA (polylactic acid), PBAT (polybutylene terephthalate), and starch. While this achieves basic degradation, it suffers from numerous technical shortcomings and cannot meet the safety, barrier properties, mechanical properties, and multi-scenario degradation requirements of food packaging. These shortcomings are detailed below: 1. Conflict between compatibility and mechanical properties: PLA is rigid but brittle, PBAT is flexible but lacks strength, and virgin starch has extremely poor compatibility with both. Films prepared by simple blending are prone to cracking, have poor puncture resistance, and have weak interlayer bonding, making them prone to delamination and peeling, and cannot meet the packaging needs of various foods such as snacks and cooked food.
[0003] 2. Insufficient water resistance and antibacterial properties: The high water absorption rate of virgin starch makes the packaging bags prone to moisture absorption and mold growth during long-term storage, which not only affects the appearance and service life of the packaging, but may also contaminate food; existing biodegradable packaging bags mostly use single antibacterial modification, which has a short-lasting antibacterial effect, and some antibacterial agents are chemical substances, posing food safety risks and failing to meet the safety requirements for direct contact with food.
[0004] 3. Safety hazards exist in the processing: Traditional preparation process uses high-temperature extrusion granulation (temperature is usually above 170℃). Under high temperature environment, bio-based raw materials such as PLA and PBAT are prone to thermal degradation and release harmful substances, which do not meet the safety standards of food-grade packaging. At the same time, high-temperature processing will cause starch gelatinization failure, further reducing the mechanical properties and water resistance of the film.
[0005] 4. Uncontrollable degradation cycle and limited application scenarios: Most existing biodegradable packaging bags can only achieve composting degradation, and the degradation speed in natural soil environment is extremely slow, which cannot meet the degradation needs of multiple scenarios such as kitchen waste and fruit and vegetable waste; moreover, there is no clear means to control the degradation cycle, either the degradation is too fast and the packaging is damaged prematurely, or the degradation is too slow and the environmental protection requirements cannot be met.
[0006] 5. Limited functionality and poor adaptability: The inner and outer layers of the packaging bag are made of the same material without functional gradient design, resulting in poor weather resistance and printability of the surface layer, and insufficient heat-sealing and antibacterial properties of the inner layer. It cannot meet multiple needs such as printing and advertising, food preservation, and heat sealing, thus limiting its application scope.
[0007] There is currently no effective solution to address the shortcomings of the existing technologies mentioned above. There is an urgent need for a fully degradable food packaging bag and its preparation method that takes into account food safety, mechanical properties, high barrier properties, long-lasting antibacterial effect, and controllable degradation in multiple scenarios, in order to fill the gap in the existing technologies. Summary of the Invention
[0008] To address the shortcomings of existing technologies and achieve the above objectives, the present invention adopts the following technical solution: An environmentally friendly and biodegradable food packaging bag adopts a three-layer gradient functional composite structure, consisting of an outer weather-resistant and printable biodegradable layer, a middle cross-linked and reinforced high-barrier layer, and an inner food-grade slow-release antibacterial and hydrophobic layer, from the outside to the inside.
[0009] Furthermore, the distribution ratio (parts by mass) of each layer is as follows: Outer weather-resistant and biodegradable printing layer: PLA 35-45 parts, PBAT 20-28 parts, hydrophobically modified lignin fiber 6-10 parts, rosin-based tackifying resin 2-4 parts, plant-based UV-resistant additive 1-3 parts; Middle layer cross-linked reinforced high barrier layer: 22-30 parts of cross-linked esterified cassava starch, 30-38 parts of PBAT, 10-15 parts of polybutylene adipate, 3-5 parts of nano-montmorillonite bio-based modified powder, and 1.5-3 parts of composite cross-linking agent; Inner food-grade slow-release antibacterial and hydrophobic layer: 40-50 parts modified chitosan grafted with PBAT, 8-12 parts polylactic acid oligomer, 2-3.5 parts plant-derived composite antibacterial agent, and 1-3 parts hydrophobic retarder.
[0010] Furthermore, the distribution ratio (parts by mass) of each layer is as follows: Outer weather-resistant and biodegradable printing layer: PLA 40 parts, PBAT 25 parts, hydrophobically modified lignin fiber 8 parts, rosin-based tackifying resin 3 parts, plant-based UV-resistant additive 2 parts; Middle layer cross-linked reinforced high barrier layer: 27 parts of cross-linked esterified modified cassava starch, 35 parts of PBAT, 12 parts of polybutylene adipate, 4 parts of nano-montmorillonite bio-based modified powder, and 2 parts of composite cross-linking agent; Inner food-grade slow-release antibacterial and hydrophobic layer: 45 parts modified chitosan grafted with PBAT, 10 parts polylactic acid oligomer, 2.5 parts plant-derived composite antibacterial agent, and 2 parts hydrophobic retarder.
[0011] Furthermore, the cross-linked esterified modified cassava starch is prepared by citric acid-epoxidized soybean oil composite cross-linking + hydrophobic esterification modification. The specific steps are as follows: cassava starch, citric acid, and epoxidized soybean oil are mixed in a mass ratio of 100:8~12:5~8, deionized water is added to adjust the water content to 10~15%, and the mixture is microwaved at 45~55℃ for 30~45min. After cooling to room temperature, the mixture is pulverized and passed through an 80~100 mesh sieve to obtain cross-linked esterified modified cassava starch.
[0012] Furthermore, the cross-linked esterified modified cassava starch is prepared by citric acid-epoxidized soybean oil composite cross-linking + hydrophobic esterification modification. The specific steps are as follows: cassava starch, citric acid, and epoxidized soybean oil are mixed in a mass ratio of 100:10:7, deionized water is added to adjust the water content to 12%, and the mixture is microwaved at 50°C for 30-45 minutes. After cooling to room temperature, the mixture is pulverized and passed through a 90-mesh sieve to obtain cross-linked esterified modified cassava starch.
[0013] Furthermore, the modified chitosan-grafted PBAT is prepared by a low-temperature melt grafting reaction. The specific steps are as follows: chitosan, PBAT, and initiator are mixed at a mass ratio of 10:40-50:0.5-1.2, and the mixture is subjected to a low-temperature melt grafting reaction at 120-135°C and 150-200 rpm for 60-90 minutes to obtain the modified chitosan-grafted PBAT.
[0014] Furthermore, the modified chitosan-grafted PBAT is prepared by a low-temperature melt grafting reaction. The specific steps are as follows: chitosan, PBAT, and initiator are mixed at a mass ratio of 10:45:1.0, and the mixture is subjected to a low-temperature melt grafting reaction at 130°C and 170 rpm for 80 min to obtain the modified chitosan-grafted PBAT.
[0015] Furthermore, the plant-derived composite antibacterial agent is a mixture of rosemary extract and tea polyphenols at a mass ratio of (2-3):1; the composite crosslinking agent is a mixture of citric acid and propylene oxide at a mass ratio of 3:1; the hydrophobic retarder is a mixture of calcium stearate and beeswax at a mass ratio of 1:1; and the hydrophobic modified lignin fiber is modified with silane coupling agent KH-550 at a modification temperature of 80-90℃ for 2-3 hours.
[0016] Furthermore, the plant-derived composite antibacterial agent is a mixture of rosemary extract and tea polyphenols at a mass ratio of 2.5:1; the composite crosslinking agent is a mixture of citric acid and propylene oxide at a mass ratio of 3:1; the hydrophobic retarder is a mixture of calcium stearate and beeswax at a mass ratio of 1:1; and the hydrophobic modified lignin fiber is modified with silane coupling agent KH-550 at a modification temperature of 85℃ for 2-3 hours.
[0017] Furthermore, in the outer weather-resistant printable biodegradable layer, the number average molecular weight of PLA is 80,000 to 120,000, and the number average molecular weight of PBAT is 100,000 to 150,000; in the inner food-grade slow-release antibacterial hydrophobic layer, the number average molecular weight of polylactic acid oligomers is 5,000 to 10,000, ensuring the flexibility and heat-sealing properties of the inner layer.
[0018] Furthermore, in the outer weather-resistant printable biodegradable layer, the number average molecular weight of PLA is 100,000 and the number average molecular weight of PBAT is 120,000; in the inner food-grade slow-release antibacterial hydrophobic layer, the number average molecular weight of polylactic acid oligomers is 8,000, ensuring the flexibility and heat-sealing properties of the inner layer.
[0019] Furthermore, the nano-montmorillonite bio-based modified powder is modified with chitosan. The specific steps are as follows: nano-montmorillonite is dispersed in deionized water, ultrasonically dispersed for 30-40 minutes, chitosan solution (mass concentration of 2-3%) is added, and the mixture is stirred and reacted at 60-70℃ for 2-3 hours. After centrifugation, washing, and drying, nano-montmorillonite bio-based modified powder is obtained.
[0020] Furthermore, the nano-montmorillonite bio-based modified powder is modified with chitosan. The specific steps are as follows: nano-montmorillonite is dispersed in deionized water, ultrasonically dispersed for 35 min, chitosan solution (mass concentration of 2.5%) is added, and the mixture is stirred and reacted at 65℃ for 2.5 h. After centrifugation, washing, and drying, nano-montmorillonite bio-based modified powder is obtained.
[0021] This invention also provides a method for preparing an environmentally friendly and biodegradable food packaging bag, comprising the following steps: Outer weather-resistant and biodegradable printing layer: PLA 40 parts, PBAT 25 parts, hydrophobically modified lignin fiber 8 parts, rosin-based tackifying resin 3 parts, plant-based UV-resistant additive 2 parts; Middle layer cross-linked reinforced high barrier layer: 27 parts of cross-linked esterified modified cassava starch, 35 parts of PBAT, 12 parts of polybutylene adipate, 4 parts of nano-montmorillonite bio-based modified powder, and 2 parts of composite cross-linking agent; Inner food-grade slow-release antibacterial and hydrophobic layer: 45 parts modified chitosan grafted with PBAT, 10 parts polylactic acid oligomer, 2.5 parts plant-derived composite antibacterial agent, and 2 parts hydrophobic retarder; Step (1): Raw material pretreatment Starch modification: Cassava starch, citric acid, and epoxidized soybean oil are mixed in a mass ratio of 100:8~12:5~8. Deionized water is added to adjust the moisture content to 10~15%. The mixture is microwaved at 45~55℃ for 30~45min. After cooling to room temperature, it is pulverized and passed through an 80~100 mesh sieve to obtain cross-linked esterified modified cassava starch for later use. Preparation of antibacterial substrate: Chitosan, PBAT and initiator are mixed at a mass ratio of 10:40-50:0.5-1.2 and subjected to low-temperature melt grafting reaction at 120-135℃ and 150-200rpm for 60-90min to obtain modified chitosan-grafted PBAT for later use. Raw material drying: PLA, PBAT, polybutylene adipate, and polylactic acid oligomers are dried at 80-90℃ for 4-6 hours, with the moisture content controlled at ≤0.5%; hydrophobic modified lignin fiber, nano-montmorillonite bio-based modified powder, plant-derived composite antibacterial agent, and other additives are dried at 60-70℃ for 2-3 hours, with the moisture content controlled at ≤0.3%.
[0022] Step (2): Melt and plasticize the three layers of material separately. The components of the outer, middle, and inner layers are mixed evenly according to the specified ratios, and then separately added to three independent single-screw extruders for low-temperature melt plasticizing, with segmented temperature control as follows: Outer extruder: feed section 135~140℃, melting section 140~145℃, die head section 145~150℃; Intermediate extruder: feed section 130-135℃, melting section 135-140℃, die head section 140-145℃; Inner extruder: feed section 125~130℃, melting section 130~135℃, die head section 135~140℃; The speed of each extruder is controlled at 180-220 rpm. After the melt is uniformly plasticized, the three layers of melt are respectively conveyed to the multi-layer co-extrusion annular die.
[0023] Step (3): Three-layer co-extrusion adhesive-free lamination and blown film forming The three-layer melt achieves molecular chain interlocking and bonding within a multi-layer co-extrusion annular die. A low-temperature, slow-speed blow-up process is employed, with the blow-up ratio controlled between 2.0 and 2.8. The melt is then cooled at a low temperature by an air ring, with the air ring temperature controlled between 15 and 25°C. After cooling to room temperature, the melt is drawn by a traction machine and wound by a winding machine to obtain a three-layer gradient composite film. The traction speed is controlled between 5 and 8 m / min to ensure uniform film thickness.
[0024] Step (4): Post-treatment of surface micro-nano cross-linking The wound composite film was subjected to low-temperature ultraviolet micro-crosslinking treatment with an ultraviolet wavelength of 254–365 nm, an irradiation time of 5–10 min, and an irradiation power of 30–50 W.
[0025] Step (5): Bag forming The post-processed composite film is fed into a bag-making machine, where it is heat-sealed and cut according to requirements. The heat-sealing temperature is controlled at 130-140℃ and the heat-sealing time is 1-2 seconds, resulting in an environmentally friendly and biodegradable food packaging bag.
[0026] Furthermore, the present invention also provides a method for preparing an environmentally friendly and biodegradable food packaging bag, comprising the following steps: drying the raw materials in step (1): drying PLA, PBAT, polybutylene adipate and polylactic acid oligomer at 85°C for 5 hours, with the moisture content controlled at ≤0.5%; drying hydrophobically modified lignin fiber, nano-montmorillonite bio-based modified powder, plant-derived composite antibacterial agent and other additives at 65°C for 2.5 hours, with the moisture content controlled at ≤0.3%.
[0027] Step (2): Melt and plasticize the three layers of material separately. The components of the outer, middle, and inner layers are mixed evenly according to the specified ratios, and then separately added to three independent single-screw extruders for low-temperature melt plasticizing, with segmented temperature control as follows: Outer extruder: feed section 138℃, melting section 142℃, die head section 147℃; Intermediate extruder: feed section 132℃, melting section 137℃, die head section 142℃; Inner extruder: feed section 127℃, melting section 132℃, die head section 137℃; Each extruder operates at 200 rpm. After the melt is uniformly plasticized, the three layers of melt are conveyed to the multi-layer co-extrusion annular die.
[0028] Step (3): Three-layer co-extrusion adhesive-free lamination and blown film forming The three-layer melt achieves molecular chain interpenetration and bonding within a multi-layer co-extrusion annular die. A low-temperature, slow-speed blow-up process is employed, with the blow-up ratio controlled at 2.5. The melt is then cooled at a low temperature by an air ring, with the air ring temperature controlled at 20°C. After cooling to room temperature, the melt is drawn by a traction machine and wound by a winding machine to obtain a three-layer gradient composite film. The traction speed is controlled at 7 m / min to ensure uniform film thickness.
[0029] Step (4): Post-treatment of surface micro-nano cross-linking The wound composite film was subjected to low-temperature ultraviolet micro-crosslinking treatment with an ultraviolet wavelength of 350nm, an irradiation time of 7min, and an irradiation power of 40W.
[0030] Step (5): Bag forming The post-processed composite film is fed into a bag-making machine, where it is heat-sealed and cut according to requirements. The heat-sealing temperature is controlled at 135℃ and the heat-sealing time is 1-2 seconds, resulting in an environmentally friendly and biodegradable food packaging bag.
[0031] The beneficial effects of this invention are: 1. Unique structure to solve the delamination problem: It adopts a three-layer gradient functional composite structure. The outer layer focuses on weather resistance and printing, the middle layer focuses on high barrier reinforcement, and the inner layer focuses on antibacterial and hydrophobic properties. The three layers are gradient adapted and achieve glue-free composite through molecular chain interpenetration and weak hydrogen bond self-adhesion. It completely solves the technical pain points of weak interlayer bonding and easy delamination of existing biodegradable packaging bags. The interlayer peel strength is ≥1.7N / 15mm.
[0032] 2. Innovative starch modification to solve the problems of water absorption and mold growth: Citric acid-epoxidized soybean oil composite crosslinking + hydrophobic esterification modification of cassava starch is used to replace traditional glycerol plasticized starch, which completely changes the hydrophilic properties of starch, reducing the water absorption rate of modified starch by more than 60%. It does not absorb moisture, mold, or become brittle during long-term storage, while improving compatibility with PBAT and enhancing the mechanical properties of the film.
[0033] 3. Food-grade safety, free from chemical pollution: The system adopts a chitosan-grafted PBAT + lignin nanofiber synergistic toughening system to replace traditional chemical compatibilizers such as maleic anhydride. All additives are plant-based or bio-based materials, with no toxic chemical substances released. The glue-free composite process avoids the risk of food contamination caused by adhesives.
[0034] 4. Low-temperature processing to preserve material properties: The low-temperature segmented plasticizing + microwave-assisted pre-modification process reduces the processing temperature by 20-30°C compared to traditional processes, avoiding thermal aging and degradation of bio-based raw materials and effectively preserving the mechanical and degradation properties of the materials. At the same time, low-temperature processing reduces energy consumption, lowers production costs, and achieves green production.
[0035] 5. Multifunctional integration and wide adaptability: It has multiple functions such as high barrier properties, long-lasting antibacterial effect, weather-resistant printing, and low-temperature freezing resistance. The water vapor transmission rate is ≤5g / (m), and the oil barrier properties are improved by more than 49% compared with ordinary biodegradable films. The plant-derived compound antibacterial agent achieves slow-release antibacterial effect, inhibiting Escherichia coli and Staphylococcus aureus with an antibacterial rate of ≥99%. The tensile strength is ≥25MPa and the puncture resistance is ≥10.5N. It can be used for packaging of various foods such as cooked food, snacks, baked goods, and frozen foods. 2 ·24h) Detailed implementation method: Specific details in the description of this invention are merely to provide a thorough understanding of the embodiments thereof; however, those skilled in the art should understand that the implementation of this invention is not limited to these details. Furthermore, well-known structures and functions have not been described or shown in detail to avoid obscuring the key points of the embodiments of this invention. Those skilled in the art can understand the specific meaning of the above terms in this invention based on the specific circumstances.
[0036] Specific embodiments of the present invention: To better understand the present invention, specific embodiments are described. It is worth emphasizing that the effects of these embodiments are not substantially different from those of various embodiments within the scope of protection of the present invention, including their respective reagents and reagent content ratios. All of them can achieve the effects described in the present invention and solve the above-mentioned problems. Other combinations are not described in detail here. The performance tests in this experiment were conducted in accordance with national standards and industry specifications, and were mainly based on the following: GB / T 10004-2008 "Dry lamination and extrusion lamination of plastic composite films and bags for packaging" - GB / T 1037-2021 Determination of Water Vapor Permeability of Plastic Films and Sheets - Cup Method (Gain and Loss Method) GB / T 16929-2025 "Test Methods for Oil Permeability of Packaging Materials" GB / T 31402-2023 "Test Method for Antibacterial Properties of Plastic Surfaces" GB / T 38082-2025 Biodegradable Plastic Shopping Bags Example 1: An environmentally friendly, biodegradable food packaging bag, with the following three-layer component ratio (parts by weight): 1. Outer weather-resistant and biodegradable printing layer: PLA 40 parts, PBAT 25 parts, hydrophobic modified lignin fiber 8 parts, rosin-based tackifying resin 3 parts, plant-based anti-UV additive 2 parts; 2. Middle layer cross-linked reinforced high barrier layer: 27 parts of cross-linked esterified modified cassava starch, 35 parts of PBAT, 12 parts of polybutylene adipate, 4 parts of nano-montmorillonite bio-based modified powder, and 2 parts of composite cross-linking agent; 3. Inner food-grade slow-release antibacterial and hydrophobic layer: 45 parts modified chitosan grafted with PBAT, 10 parts polylactic acid oligomer, 2.5 parts plant-derived composite antibacterial agent, and 2 parts hydrophobic retarder; Among them, the preparation of cross-linked esterified modified cassava starch: cassava starch, citric acid and epoxidized soybean oil are mixed in a mass ratio of 100:10:7, deionized water is added to adjust the water content to 12%, microwave reaction is carried out at 50℃ for 38 min, and after cooling to room temperature, it is pulverized and passed through a 90-mesh sieve. Preparation of modified chitosan grafted with PBAT: chitosan, PBAT and initiator were mixed at a mass ratio of 10:45:1 and subjected to low-temperature melt grafting reaction at 130℃ and 170rpm for 80min. The plant-derived compound antibacterial agent is a mixture of rosemary extract and tea polyphenols at a mass ratio of 2.5:1; the compound crosslinking agent is a mixture of citric acid and propylene oxide at a mass ratio of 3:1; the hydrophobic retarder is a mixture of calcium stearate and beeswax at a mass ratio of 1:1; the hydrophobic modified lignin fiber is modified with silane coupling agent KH-550 at 85℃ for 2.5h; the nano-montmorillonite bio-based modified powder is modified with chitosan, specifically: nano-montmorillonite is dispersed in deionized water, ultrasonically dispersed for 35min, a chitosan solution with a mass concentration of 2.5% is added, and the mixture is stirred and reacted at 65℃ for 2.5h, followed by centrifugation, washing, and drying.
[0037] PLA has a number-average molecular weight of 100,000, and PBAT has a number-average molecular weight of 120,000; in the inner food-grade slow-release antibacterial hydrophobic layer, the polylactic acid oligomer has a number-average molecular weight of 8,000.
[0038] The method for preparing the above-mentioned food packaging bags includes the following steps: Step 1: Raw material pretreatment 1.1 Cross-linked esterified cassava starch and modified chitosan-grafted PBAT were prepared according to the above method and set aside for later use; 1.2 PLA, PBAT, polybutylene adipate, and polylactic acid oligomers were dried at 85℃ for 5 hours, with the moisture content controlled at ≤0.5%; hydrophobic modified lignin fiber, nano-montmorillonite bio-based modified powder, plant-derived composite antibacterial agent, and other additives were dried at 65℃ for 2.5 hours, with the moisture content controlled at ≤0.3%.
[0039] Step 2: Melt and plasticize the three layers of material separately. The components of the outer, middle, and inner layers are mixed evenly according to the specified ratios, and then added separately to three independent single-screw extruders, with segmented temperature control as follows: Outer extruder: feed section 138℃, melting section 142℃, die head section 147℃; Intermediate extruder: feed section 132℃, melting section 137℃, die head section 142℃; Inner extruder: feed section 127℃, melting section 132℃, die head section 137℃; Each extruder speed is controlled at 200 rpm. After the melt is uniformly plasticized, the three-layer melt is conveyed to the multi-layer co-extrusion annular die.
[0040] Step 3: Three-layer co-extrusion adhesive-free lamination and blown film forming After the three-layer melt is combined in the die head, it is cooled to room temperature with a blow-up ratio of 2.5 and an air ring temperature of 20°C. Then, it is pulled and wound at a speed of 7m / min to obtain a three-layer gradient composite film.
[0041] Step 4: Post-treatment of surface micro-nano cross-linking The composite film was irradiated with ultraviolet light at a wavelength of 350 nm and a power of 40 W for 7 minutes to complete the surface micro-nano crosslinking.
[0042] Step 5: Bag forming The composite film is fed into a bag-making machine, where it is heat-sealed and cut at 135°C for 1.5 seconds to obtain the target food packaging bag.
[0043] The food packaging bag prepared in this embodiment has an interlayer peel strength of 2.3 N / 15 mm, a water vapor permeability of 3.8 g / (m), an oil barrier property that is 52% higher than that of ordinary biodegradable films, an Escherichia coli inhibition rate of 99.7%, a Staphylococcus aureus inhibition rate of 99.6%, a tensile strength of 28 MPa, a puncture resistance of 12.7 N, complete degradation in industrial compost in 60 days, and complete degradation in natural soil in 120 days, with no harmful residues, and meets food-grade safety standards. 2 ·24h) Example 2: An environmentally friendly, biodegradable food packaging bag, with the following three-layer component ratio (parts by weight): 1. Outer weather-resistant and biodegradable printing layer: PLA 35 parts, PBAT 20 parts, hydrophobic modified lignin fiber 6 parts, rosin-based tackifying resin 2 parts, plant-based anti-UV additive 1 part; 2. Middle layer cross-linked reinforced high barrier layer: 22 parts of cross-linked esterified modified cassava starch, 30 parts of PBAT, 10 parts of polybutylene adipate, 3 parts of nano-montmorillonite bio-based modified powder, and 1.5 parts of composite cross-linking agent; 3. Inner food-grade slow-release antibacterial and hydrophobic layer: 40 parts modified chitosan grafted with PBAT, 8 parts polylactic acid oligomer, 2 parts plant-derived composite antibacterial agent, and 1 part hydrophobic retarder; Among them, the preparation of cross-linked esterified modified cassava starch: cassava starch, citric acid and epoxidized soybean oil are mixed in a mass ratio of 100:8:5, deionized water is added to adjust the water content to 10%, microwave reaction is carried out at 45℃ for 30 min, and after cooling to room temperature, it is pulverized and passed through an 80-mesh sieve. Preparation of modified chitosan grafted with PBAT: chitosan, PBAT and initiator were mixed at a mass ratio of 10:40:0.5 and subjected to low-temperature melt grafting reaction at 120℃ and 150rpm for 60min. The plant-derived compound antibacterial agent is a mixture of rosemary extract and tea polyphenols at a mass ratio of 2:1; the compound crosslinking agent is a mixture of citric acid and propylene oxide at a mass ratio of 3:1; the hydrophobic retarder is a mixture of calcium stearate and beeswax at a mass ratio of 1:1; the hydrophobic modified lignin fiber is modified with silane coupling agent KH-550 at 80℃ for 2 hours; the nano-montmorillonite bio-based modified powder is modified with chitosan, specifically: nano-montmorillonite is dispersed in deionized water, ultrasonically dispersed for 30 minutes, a 2% chitosan solution is added, stirred and reacted at 60℃ for 2 hours, centrifuged, washed, and dried.
[0044] PLA has a number-average molecular weight of 80,000, and PBAT has a number-average molecular weight of 100,000; in the inner food-grade slow-release antibacterial hydrophobic layer, the polylactic acid oligomer has a number-average molecular weight of 5,000.
[0045] The method for preparing the above-mentioned food packaging bags includes the following steps: Step 1: Raw material pretreatment 1.1 Cross-linked esterified cassava starch and modified chitosan-grafted PBAT were prepared according to the above method and set aside for later use; 1.2 The PLA, PBAT, polybutylene adipate, and polylactic acid oligomer were dried at 80℃ for 4 hours, and the moisture content was controlled to be ≤0.5%; the hydrophobic modified lignin fiber, nano-montmorillonite bio-based modified powder, plant-derived composite antibacterial agent and other additives were dried at 60℃ for 2 hours, and the moisture content was controlled to be ≤0.3%.
[0046] Step 2: Melt and plasticize the three layers of material separately. The components of the outer, middle, and inner layers are mixed evenly according to the specified ratios, and then added separately to three independent single-screw extruders, with segmented temperature control as follows: Outer extruder: feed section 135℃, melting section 140℃, die head section 145℃; Intermediate extruder: feed section 130℃, melting section 135℃, die head section 140℃; Inner extruder: feed section 125℃, melting section 130℃, die head section 135℃; Each extruder operates at 180 rpm. After the melt is uniformly plasticized, the three-layer melt is conveyed to the multi-layer co-extrusion annular die.
[0047] Step 3: Three-layer co-extrusion adhesive-free lamination and blown film forming After the three-layer melt is bonded in the die head, it is cooled to room temperature with a blow-up ratio of 2.0 and an air ring temperature of 15℃. Then, it is pulled and wound at a speed of 5m / min to obtain a three-layer gradient composite film.
[0048] Step 4: Post-treatment of surface micro-nano cross-linking The composite film was irradiated with ultraviolet light at a wavelength of 254 nm and a power of 30 W for 5 minutes to complete the surface micro-nano crosslinking.
[0049] Step 5: Bag forming The composite film is fed into a bag-making machine, where it is heat-sealed and cut at 130°C for 1 second to obtain the target food packaging bag.
[0050] The food packaging bag prepared in this embodiment has an interlayer peel strength of 2.1 N / 15 mm, a water vapor permeability of 4.1 g / (m), an oil barrier property that is 49% higher than that of ordinary biodegradable films, an Escherichia coli inhibition rate of 99.4%, a Staphylococcus aureus inhibition rate of 99.5%, a tensile strength of 26 MPa, a puncture resistance of 11.3 N, complete degradation in industrial compost in 67 days, and complete degradation in natural soil in 125 days, with no harmful residues, and meets food-grade safety standards. 2 ·24h) Example 3: An environmentally friendly, biodegradable food packaging bag, with the following three-layer component ratio (parts by weight): 1. Outer weather-resistant and biodegradable printing layer: PLA 45 parts, PBAT 28 parts, hydrophobic modified lignin fiber 10 parts, rosin-based tackifying resin 4 parts, plant-based UV-resistant additive 3 parts; 2. Middle layer cross-linked reinforced high barrier layer: 30 parts of cross-linked esterified modified cassava starch, 38 parts of PBAT, 15 parts of polybutylene adipate, 5 parts of nano-montmorillonite bio-based modified powder, and 3 parts of composite cross-linking agent; 3. Inner food-grade slow-release antibacterial and hydrophobic layer: 50 parts modified chitosan grafted with PBAT, 12 parts polylactic acid oligomer, 3.5 parts plant-derived composite antibacterial agent, and 3 parts hydrophobic retarder; Among them, the preparation of cross-linked esterified modified cassava starch: cassava starch, citric acid and epoxidized soybean oil are mixed in a mass ratio of 100:12:8, deionized water is added to adjust the water content to 15%, microwave reaction is carried out at 55℃ for 45 min, and after cooling to room temperature, it is pulverized and passed through a 100-mesh sieve. Preparation of modified chitosan grafted with PBAT: chitosan, PBAT and initiator were mixed at a mass ratio of 10:50:1.2 and subjected to low-temperature melt grafting reaction at 135℃ and 200rpm for 90min. The plant-derived compound antibacterial agent is a mixture of rosemary extract and tea polyphenols at a mass ratio of 3:1; the compound crosslinking agent is a mixture of citric acid and propylene oxide at a mass ratio of 3:1; the hydrophobic retarder is a mixture of calcium stearate and beeswax at a mass ratio of 1:1; the hydrophobic modified lignin fiber is modified with silane coupling agent KH-550 at 90℃ for 3h; the nano-montmorillonite bio-based modified powder is modified with chitosan, specifically: nano-montmorillonite is dispersed in deionized water, ultrasonically dispersed for 40min, a 3% chitosan solution is added, stirred and reacted at 70℃ for 3h, centrifuged, washed, and dried.
[0051] The number-average molecular weight of PLA is 120,000, and the number-average molecular weight of PBAT is 150,000; in the inner food-grade slow-release antibacterial hydrophobic layer, the number-average molecular weight of polylactic acid oligomers is 10,000.
[0052] The method for preparing the above-mentioned food packaging bags includes the following steps: Step 1: Raw material pretreatment 1.1 Cross-linked esterified cassava starch and modified chitosan-grafted PBAT were prepared according to the above method and set aside for later use; 1.2 PLA, PBAT, polybutylene adipate, and polylactic acid oligomers were dried at 90℃ for 6 hours, with the moisture content controlled at ≤0.5%; hydrophobic modified lignin fiber, nano-montmorillonite bio-based modified powder, plant-derived composite antibacterial agent, and other additives were dried at 70℃ for 3 hours, with the moisture content controlled at ≤0.3%.
[0053] Step 2: Melt and plasticize the three layers of material separately. The components of the outer, middle, and inner layers are mixed evenly according to the specified ratios, and then added separately to three independent single-screw extruders, with segmented temperature control as follows: Outer extruder: feed section 140℃, melting section 145℃, die head section 150℃; Intermediate extruder: Feed section 135℃, Melting section 140℃, Die head section 145℃; Inner extruder: feed section 130℃, melting section 135℃, die head section 140℃; Each extruder speed is controlled at 220 rpm. After the melt is uniformly plasticized, the three-layer melt is conveyed to the multi-layer co-extrusion annular die.
[0054] Step 3: Three-layer co-extrusion adhesive-free lamination and blown film forming After the three-layer melt is bonded in the die head, it is cooled to room temperature with a blow-up ratio of 2.8 and an air ring temperature of 25°C. Then, it is pulled and wound at a speed of 8m / min to obtain a three-layer gradient composite film.
[0055] Step 4: Post-treatment of surface micro-nano cross-linking The composite film was irradiated with ultraviolet light at a wavelength of 365nm and a power of 50W for 10 minutes to complete the surface micro-nano crosslinking.
[0056] Step 5: Bag forming The composite film is fed into a bag-making machine, where it is heat-sealed and cut at 140°C for 2 seconds to obtain the target food packaging bag.
[0057] The food packaging bag prepared in this embodiment has an interlayer peel strength of 1.7 N / 15 mm, a water vapor permeability of 4.5 g / (m), an oil barrier property that is 50% higher than that of ordinary biodegradable films, an Escherichia coli inhibition rate of 99.3%, a Staphylococcus aureus inhibition rate of 99.2%, a tensile strength of 25 MPa, a puncture resistance of 10.5 N, complete degradation in industrial compost in 70 days, and complete degradation in natural soil in 130 days, with no harmful residues, and meets food-grade safety standards. 2 ·24h) Comparative Example 1: An environmentally friendly, biodegradable food packaging bag, with the following three-layer component ratio (parts by weight): 1. Outer weather-resistant and biodegradable printing layer: PLA 30 parts, PBAT 15 parts, hydrophobically modified lignin fiber 5 parts, rosin-based tackifying resin 1 part, plant-based UV-resistant additive 0.5 parts; 2. Middle layer cross-linked reinforced high barrier layer: 20 parts of cross-linked esterified modified cassava starch, 25 parts of PBAT, 8 parts of polybutylene adipate, 1 part of nano-montmorillonite bio-based modified powder, and 1 part of composite cross-linking agent; 3. Inner food-grade slow-release antibacterial and hydrophobic layer: 35 parts modified chitosan grafted with PBAT, 7 parts polylactic acid oligomer, 1 part plant-derived composite antibacterial agent, and 0.5 parts hydrophobic retarder; Among them, the preparation of cross-linked esterified modified cassava starch: cassava starch, citric acid and epoxidized soybean oil are mixed in a mass ratio of 100:5:3, deionized water is added to adjust the water content to 8%, microwave reaction is carried out at 40℃ for 30 min, and after cooling to room temperature, it is pulverized and passed through an 80-mesh sieve. Preparation of modified chitosan grafted with PBAT: chitosan, PBAT and initiator were mixed at a mass ratio of 10:35:0.2 and subjected to low-temperature melt grafting reaction at 110℃ and 140rpm for 50min. The plant-derived compound antibacterial agent is a mixture of rosemary extract and tea polyphenols at a mass ratio of 1:1; the compound crosslinking agent is a mixture of citric acid and propylene oxide at a mass ratio of 2:1; the hydrophobic retarder is a mixture of calcium stearate and beeswax at a mass ratio of 0.5:1; the hydrophobic modified lignin fiber is modified with silane coupling agent KH-550 at 75℃ for 1h; the nano-montmorillonite bio-based modified powder is modified with chitosan, specifically: nano-montmorillonite is dispersed in deionized water, ultrasonically dispersed for 20min, a 1% chitosan solution is added, stirred and reacted at 50℃ for 1h, centrifuged, washed, and dried.
[0058] PLA has a number-average molecular weight of 70,000, and PBAT has a number-average molecular weight of 90,000; in the inner food-grade slow-release antibacterial hydrophobic layer, the polylactic acid oligomer has a number-average molecular weight of 4,000.
[0059] The method for preparing the above-mentioned food packaging bags includes the following steps: Step 1: Raw material pretreatment 1.1 Cross-linked esterified cassava starch and modified chitosan-grafted PBAT were prepared according to the above method and set aside for later use; 1.2 PLA, PBAT, polybutylene adipate, and polylactic acid oligomers were dried at 75°C for 3 hours, with the moisture content controlled to ≤0.5%; hydrophobic modified lignin fibers, nano-montmorillonite bio-based modified powder, plant-derived composite antibacterial agents, and other additives were dried at 50°C for 1 hour, with the moisture content controlled to ≤0.3%.
[0060] Step 2: Melt and plasticize the three layers of material separately. The components of the outer, middle, and inner layers are mixed evenly according to the specified ratios, and then added separately to three independent single-screw extruders, with segmented temperature control as follows: Outer extruder: feed section 130℃, melting section 135℃, die head section 140℃; Intermediate extruder: feed section 125℃, melting section 130℃, die head section 135℃; Inner extruder: feed section 120℃, melting section 125℃, die head section 130℃; Each extruder speed is controlled at 170 rpm. After the melt is uniformly plasticized, the three-layer melt is conveyed to the multi-layer co-extrusion annular die.
[0061] Step 3: Three-layer co-extrusion adhesive-free lamination and blown film forming After the three-layer melt is bonded in the die head, it is cooled to room temperature with a blow-up ratio of 1.0 and an air ring temperature of 10℃. Then, it is pulled and wound at a speed of 3m / min to obtain a three-layer gradient composite film.
[0062] Step 4: Post-treatment of surface micro-nano cross-linking The composite film was irradiated with ultraviolet light at a wavelength of 240 nm and a power of 25 W for 3 minutes to complete the surface micro-nano crosslinking.
[0063] Step 5: Bag forming The composite film is fed into a bag-making machine, where it is heat-sealed and cut at 120°C for 1 second to obtain the target food packaging bag.
[0064] The food packaging bag prepared in this embodiment has an interlayer peel strength of 1.5 N / 15 mm, a water vapor permeability of 5.3 g / (m), an oil barrier property that is 20% higher than that of ordinary biodegradable films, an Escherichia coli inhibition rate of 97.2%, a Staphylococcus aureus inhibition rate of 98.5%, a tensile strength of 20 MPa, a puncture resistance of 8.3 N, and is not completely degraded in industrial compost after 90 days and in natural soil after 150 days. 2 ·24h) Comparative Example 2: An environmentally friendly, biodegradable food packaging bag, with the following three-layer component ratio (parts by weight): 1. Outer weather-resistant and biodegradable printing layer: PLA 50 parts, PBAT 30 parts, hydrophobic modified lignin fiber 15 parts, rosin-based tackifying resin 5 parts, plant-based anti-UV additive 5 parts; 2. Middle layer cross-linked reinforced high barrier layer: 35 parts of cross-linked esterified modified cassava starch, 40 parts of PBAT, 20 parts of polybutylene adipate, 7 parts of nano-montmorillonite bio-based modified powder, and 5 parts of composite cross-linking agent; 3. Inner food-grade slow-release antibacterial and hydrophobic layer: 55 parts modified chitosan grafted with PBAT, 15 parts polylactic acid oligomer, 4 parts plant-derived composite antibacterial agent, and 5 parts hydrophobic retarder; Among them, the preparation of cross-linked esterified modified cassava starch: cassava starch, citric acid and epoxidized soybean oil are mixed in a mass ratio of 100:15:10, deionized water is added to adjust the water content to 18%, microwave reaction is carried out at 60℃ for 60 min, and after cooling to room temperature, it is pulverized and passed through a 120 mesh sieve. Preparation of modified chitosan grafted with PBAT: chitosan, PBAT and initiator were mixed at a mass ratio of 10:60:1.5 and subjected to low-temperature melt grafting reaction at 140℃ and 220rpm for 100min. The plant-derived compound antibacterial agent is a mixture of rosemary extract and tea polyphenols at a mass ratio of 5:1; the compound crosslinking agent is a mixture of citric acid and propylene oxide at a mass ratio of 4:1; the hydrophobic retarder is a mixture of calcium stearate and beeswax at a mass ratio of 0.5:1; the hydrophobic modified lignin fiber is modified with silane coupling agent KH-550 at 100℃ for 5h; the nano-montmorillonite bio-based modified powder is modified with chitosan, specifically: nano-montmorillonite is dispersed in deionized water, ultrasonically dispersed for 50min, a 5% chitosan solution is added, stirred and reacted at 80℃ for 4h, centrifuged, washed, and dried.
[0065] The number average molecular weight of PLA is 150,000, and the number average molecular weight of PBAT is 170,000; in the inner food-grade slow-release antibacterial hydrophobic layer, the number average molecular weight of polylactic acid oligomers is 15,000.
[0066] The method for preparing the above-mentioned food packaging bags includes the following steps: Step 1: Raw material pretreatment 1.1 Cross-linked esterified cassava starch and modified chitosan-grafted PBAT were prepared according to the above method and set aside for later use; 1.2 The PLA, PBAT, polybutylene adipate, and polylactic acid oligomers were dried at 100℃ for 8 hours, and the moisture content was controlled to be ≤0.5%; the hydrophobic modified lignin fiber, nano-montmorillonite bio-based modified powder, plant-derived composite antibacterial agent and other additives were dried at 80℃ for 4 hours, and the moisture content was controlled to be ≤0.3%.
[0067] Step 2: Melt and plasticize the three layers of material separately. The components of the outer, middle, and inner layers are mixed evenly according to the specified ratios, and then added separately to three independent single-screw extruders, with segmented temperature control as follows: Outer extruder: feed section 145℃, melting section 150℃, die head section 155℃; Intermediate extruder: feed section 140℃, melting section 145℃, die head section 150℃; Inner extruder: feed section 135℃, melting section 140℃, die head section 145℃; Each extruder speed is controlled at 230 rpm. After the melt is uniformly plasticized, the three-layer melt is conveyed to the multi-layer co-extrusion annular die.
[0068] Step 3: Three-layer co-extrusion adhesive-free lamination and blown film forming After the three-layer melt is bonded in the die head, it is cooled to room temperature with a blow-up ratio of 3.0 and an air ring temperature of 30℃. Then it is pulled and wound at a speed of 10m / min to obtain a three-layer gradient composite film.
[0069] Step 4: Post-treatment of surface micro-nano cross-linking The composite film was irradiated with ultraviolet light at a wavelength of 380 nm and a power of 60 W for 15 min to complete the surface micro-nano crosslinking.
[0070] Step 5: Bag forming The composite film is fed into a bag-making machine, where it is heat-sealed and cut at 150°C for 5 seconds to obtain the target food packaging bag.
[0071] The food packaging bag prepared in this embodiment has an interlayer peel strength of 1.3 N / 15 mm and a water vapor transmission rate of 5.7 g / (m²). 2 (24h), the oil barrier properties are 17% higher than ordinary biodegradable films, the antibacterial rate of Escherichia coli is 97.8%, the antibacterial rate of Staphylococcus aureus is 98.2%, the tensile strength is 21MPa, the puncture resistance is 7.9N, industrial compost is not completely degraded after 90 days, and natural soil is not completely degraded after 150 days.
Claims
1. An environmentally friendly and biodegradable food packaging bag, which adopts a three-layer gradient functional composite structure, consisting of an outer weather-resistant and printable biodegradable layer, a middle cross-linked and reinforced high-barrier layer, and an inner food-grade slow-release antibacterial and hydrophobic layer, from the outside to the inside.
2. The environmentally friendly biodegradable food packaging bag according to claim 1, characterized in that, The distribution ratio (parts by mass) of each layer is as follows: Outer weather-resistant and biodegradable printing layer: PLA 35-45 parts, PBAT 20-28 parts, hydrophobically modified lignin fiber 6-10 parts, rosin-based tackifying resin 2-4 parts, plant-based UV-resistant additive 1-3 parts; Middle layer cross-linked reinforced high barrier layer: 22-30 parts of cross-linked esterified cassava starch, 30-38 parts of PBAT, 10-15 parts of polybutylene adipate, 3-5 parts of nano-montmorillonite bio-based modified powder, and 1.5-3 parts of composite cross-linking agent; Inner food-grade slow-release antibacterial and hydrophobic layer: 40-50 parts modified chitosan grafted with PBAT, 8-12 parts polylactic acid oligomer, 2-3.5 parts plant-derived composite antibacterial agent, and 1-3 parts hydrophobic retarder.
3. The environmentally friendly biodegradable food packaging bag according to claim 1, characterized in that, The distribution ratio (parts by mass) of each layer is as follows: Outer weather-resistant and biodegradable printing layer: PLA 40 parts, PBAT 25 parts, hydrophobically modified lignin fiber 8 parts, rosin-based tackifying resin 3 parts, plant-based UV-resistant additive 2 parts; Middle layer cross-linked reinforced high barrier layer: 27 parts of cross-linked esterified modified cassava starch, 35 parts of PBAT, 12 parts of polybutylene adipate, 4 parts of nano-montmorillonite bio-based modified powder, and 2 parts of composite cross-linking agent; Inner food-grade slow-release antibacterial and hydrophobic layer: 45 parts modified chitosan grafted with PBAT, 10 parts polylactic acid oligomer, 2.5 parts plant-derived composite antibacterial agent, and 2 parts hydrophobic retarder.
4. The environmentally friendly biodegradable food packaging bag according to claim 1, characterized in that, The cross-linked esterified modified cassava starch is prepared by citric acid-epoxidized soybean oil composite cross-linking + hydrophobic esterification modification. The specific steps are as follows: cassava starch, citric acid, and epoxidized soybean oil are mixed in a mass ratio of 100:8~12:5~8, deionized water is added to adjust the water content to 10~15%, and the mixture is microwaved at 45~55℃ for 30~45min. After cooling to room temperature, the mixture is pulverized and passed through an 80~100 mesh sieve to obtain cross-linked esterified modified cassava starch.
5. The environmentally friendly biodegradable food packaging bag according to claim 1, characterized in that, The modified chitosan-grafted PBAT was prepared by a low-temperature melt grafting reaction. The specific steps are as follows: chitosan, PBAT, and initiator are mixed at a mass ratio of 10:40-50:0.5-1.2, and the mixture is subjected to a low-temperature melt grafting reaction at 120-135℃ and 150-200 rpm for 60-90 minutes to obtain modified chitosan-grafted PBAT.
6. The environmentally friendly biodegradable food packaging bag according to claim 1, characterized in that, The plant-derived composite antibacterial agent is a mixture of rosemary extract and tea polyphenols at a mass ratio of (2-3):1; the composite crosslinking agent is a mixture of citric acid and propylene oxide at a mass ratio of 3:1; the hydrophobic retarder is a mixture of calcium stearate and beeswax at a mass ratio of 1:1; the hydrophobic modified lignin fiber is modified with silane coupling agent KH-550 at a modification temperature of 80-90℃ for 2-3 hours.
7. The environmentally friendly biodegradable food packaging bag according to claim 1, characterized in that, In the outer weather-resistant, printable, and biodegradable layer, the number-average molecular weight of PLA is 80,000–120,000, and the number-average molecular weight of PBAT is 100,000–150,000; in the inner food-grade slow-release antibacterial hydrophobic layer, the number-average molecular weight of polylactic acid oligomers is 5,000–10,000, ensuring the flexibility and heat-sealing properties of the inner layer.
8. The environmentally friendly biodegradable food packaging bag according to claim 1, characterized in that, The nano-montmorillonite bio-based modified powder is modified with chitosan. The specific steps are as follows: nano-montmorillonite is dispersed in deionized water and ultrasonically dispersed for 30-40 minutes. Chitosan solution (mass concentration of 2-3%) is added and stirred at 60-70℃ for 2-3 hours. After centrifugation, washing and drying, nano-montmorillonite bio-based modified powder is obtained.
9. A method for preparing an environmentally friendly and biodegradable food packaging bag, comprising the following steps: Outer weather-resistant and biodegradable printing layer: PLA 40 parts, PBAT 25 parts, hydrophobically modified lignin fiber 8 parts, rosin-based tackifying resin 3 parts, plant-based UV-resistant additive 2 parts; Middle layer cross-linked reinforced high barrier layer: 27 parts of cross-linked esterified modified cassava starch, 35 parts of PBAT, 12 parts of polybutylene adipate, 4 parts of nano-montmorillonite bio-based modified powder, and 2 parts of composite cross-linking agent; Inner food-grade slow-release antibacterial and hydrophobic layer: 45 parts modified chitosan grafted with PBAT, 10 parts polylactic acid oligomer, 2.5 parts plant-derived composite antibacterial agent, and 2 parts hydrophobic retarder; Step (1): Raw material pretreatment Starch modification: Cassava starch, citric acid, and epoxidized soybean oil are mixed in a mass ratio of 100:8~12:5~8. Deionized water is added to adjust the moisture content to 10~15%. The mixture is microwaved at 45~55℃ for 30~45min. After cooling to room temperature, it is pulverized and passed through an 80~100 mesh sieve to obtain cross-linked esterified modified cassava starch for later use. Preparation of antibacterial substrate: Chitosan, PBAT and initiator are mixed at a mass ratio of 10:40-50:0.5-1.2 and subjected to low-temperature melt grafting reaction at 120-135℃ and 150-200rpm for 60-90min to obtain modified chitosan-grafted PBAT for later use. Raw material drying: PLA, PBAT, polybutylene adipate, and polylactic acid oligomers were dried at 80–90℃ for 4–6 hours, with the moisture content controlled to ≤0.5%; hydrophobically modified lignin fibers, nano-montmorillonite bio-based modified powder, plant-derived composite antibacterial agents, and other additives were dried at 60–70℃ for 2–3 hours, with the moisture content controlled to ≤0.3%. Step (2): Melt and plasticize the three layers of material separately. The components of the outer, middle, and inner layers are mixed evenly according to the specified ratios, and then separately added to three independent single-screw extruders for low-temperature melt plasticizing, with segmented temperature control as follows: Outer extruder: feed section 135~140℃, melting section 140~145℃, die head section 145~150℃; Intermediate extruder: feed section 130-135℃, melting section 135-140℃, die head section 140-145℃; Inner extruder: feed section 125~130℃, melting section 130~135℃, die head section 135~140℃; The speed of each extruder is controlled at 180-220 rpm. After the melt is uniformly plasticized, the three layers of melt are respectively conveyed to the multi-layer co-extrusion annular die. Step (3): Three-layer co-extrusion adhesive-free lamination and blown film forming The three-layer melt achieves molecular chain interlocking and bonding within a multi-layer co-extrusion annular die. A low-temperature, slow-speed blow-up process is employed, with the blow-up ratio controlled between 2.0 and 2.
8. The melt is then cooled at a low temperature by an air ring, with the air ring temperature controlled between 15 and 25°C. After cooling to room temperature, the melt is drawn by a traction machine and wound by a winding machine to obtain a three-layer gradient composite film. The traction speed is controlled between 5 and 8 m / min to ensure uniform film thickness. Step (4): Post-treatment of surface micro-nano cross-linking The wound composite film was subjected to low-temperature ultraviolet micro-crosslinking treatment with an ultraviolet wavelength of 254–365 nm, an irradiation time of 5–10 min, and an irradiation power of 30–50 W. Step (5): Bag forming The post-processed composite film is fed into a bag making machine, where it is heat-sealed and cut according to requirements. The heat-sealing temperature is controlled at 130-140℃ and the heat-sealing time is 1-2 seconds to obtain an environmentally friendly and biodegradable food packaging bag. The method for preparing the environmentally friendly biodegradable food packaging bag according to claim 9 includes the following steps: In step (1), the raw materials were dried as follows: PLA, PBAT, polybutylene adipate, and polylactic acid oligomers were dried at 85°C for 5 hours, with the moisture content controlled at ≤0.5%; hydrophobic modified lignin fibers, nano-montmorillonite bio-based modified powder, plant-derived composite antibacterial agents, and other additives were dried at 65°C for 2.5 hours, with the moisture content controlled at ≤0.3%. Step (2): Melt and plasticize the three layers of material separately. The components of the outer, middle, and inner layers are mixed evenly according to the specified ratios, and then separately added to three independent single-screw extruders for low-temperature melt plasticizing, with segmented temperature control as follows: Outer extruder: feed section 138℃, melting section 142℃, die head section 147℃; Intermediate extruder: feed section 132℃, melting section 137℃, die head section 142℃; Inner extruder: feed section 127℃, melting section 132℃, die head section 137℃; Each extruder speed is controlled at 200 rpm. After the melt is uniformly plasticized, the three layers of melt are respectively conveyed to the multi-layer co-extrusion annular die. Step (3): Three-layer co-extrusion adhesive-free lamination and blown film forming The three-layer melt achieves molecular chain interlocking and bonding within a multi-layer co-extrusion annular die. A low-temperature, slow-speed blowing process is employed, with the blowing ratio controlled at 2.
5. The melt is then cooled at a low temperature by an air ring, with the air ring temperature controlled at 20°C. After cooling to room temperature, the melt is drawn by a traction machine and wound by a winding machine to obtain a three-layer gradient composite film. The traction speed is controlled at 7 m / min to ensure uniform film thickness. Step (4): Post-treatment of surface micro-nano cross-linking The wound composite film was subjected to low-temperature ultraviolet micro-crosslinking treatment with an ultraviolet wavelength of 350nm, an irradiation time of 7min, and an irradiation power of 40W. Step (5): Bag forming The post-processed composite film is fed into a bag-making machine, where it is heat-sealed and cut according to requirements. The heat-sealing temperature is controlled at 135℃ and the heat-sealing time is 1-2 seconds, resulting in an environmentally friendly and biodegradable food packaging bag.